Preferensi Nasabah Pelaku UMKM dalam Menggunakan Pembiayaan Bank Syariah Indonesia (Studi Kasus UMKM Kota Mataram Nusa Tenggara Barat) - muhammad Rafi’i Sanjani; Indah Fitriana Sari (ITB AAS INDONESIA Surakarta, 2021)
One of the main problems encountered by the micro, small, and medium enterprises (SMEs) is the capital of the injustice system in bank lending rates and the high cost of conventional interest rate for the borrower (micro, small, and medium enterprises). As a result, SMEs are looking for other alternatives to increase capital by proposing financing to Islamic banking. The purpose of this study is to examine the preference of SMEs to choose financing in Bank Syariah Indonesia (BSI) in the Municipality of Mataram West Nusa Tenggara and to determine the effect of each preference, as well as to determine the most dominant preference behind this preference. The object of this research is customers (SMEs actors) who have used sharia financing at the Bank Syariah Indonesia (BSI) in the municipality of Mataram West Nusa Tenggara. The sampling technique in this research uses purposive sampling, while the primary data is collected by a questionnaire. Data were analyzed using multiple linear regression techniques. The results of this study indicate that preference of SMEs in choosing Islamic finance in Bank Syariah Indonesia (BSI) in the Municipality of Mataram West Nusa Tenggara is positively and significantly driven by the intention to run the Islamic law, profit-sharing, financing terms, service of employees, and quick process of granting financing which was accounted to 87.8%. That is, provided that the intention to enforce Sharia Law is getting stronger, profit-sharing is more equitable, financing requirements is much lighter, the service by the employee is more qualified, and the process of financing is more quickly, the preference of SMEs in choosing to use Islamic finance in Bank Syariah Indonesia (BSI) in the Municipality of Mataram West Nusa Tenggara will also be higher. Among the five of preferences, the most dominantly influential preferences is a service provided by the employee, followed by a strong intention to implement Islamic law, the speed of the process of financing, financing requirements, and profit-sharing system applied.